The Poetics of Letters in English Literature - Narzulloyeva Maftuna Nusratillo qizi (International Scientific and Current Research Conferences, 2025)
This paper explores the poetics of letter-writing in English literature, focusing on how letters function not only as a narrative device but also as a medium for expressing inner emotions, relationships, and social structures. Drawing on key works by authors such as Samuel Richardson, Jane Austen, and Virginia Woolf, this study analyzes how epistolary forms contribute to character development and thematic depth. By examining both the formal qualities and emotional undertones of literary letters, the paper highlights the unique literary value of the epistolary form within various historical contexts.